2001
DOI: 10.1086/319750
|View full text |Cite
|
Sign up to set email alerts
|

Constancy of Distribution of Serogroups of Invasive Pneumococcal Isolates Among Children: Experience during 4 Decades

Abstract: Serogroups of pneumococci that caused bacteremia or meningitis in children were examined from 1981 through 1998 at Boston City Hospital/Boston Medical Center. There were 410 episodes of pneumococcal bacteremia (13--36 cases per year), of which 14 occurred in human immunodeficiency virus (HIV)--infected children and 9 occurred in children with sickle-cell disease. The 7 most common serogroups were 14 (30.7% of isolates), 19 (11.7%), 6 (11%), 18 (10.7%), 9 (7.6%), 23 (7.3%), and 4 (5.6%). The rate of episodes du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
29
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 22 publications
1
29
0
Order By: Relevance
“…Serotyping uses a series of antibodies to detect antigens on the surface of bacteria that have been shown demonstrate antigenic variability (12,149,210). Serotyping methods have been used for decades for the taxonomic grouping of a number of bacterial pathogen species and remain important for typing Salmonella, Legionella, Shigella, and Streptococcus pneumoniae isolates.…”
Section: Phenotypic Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Serotyping uses a series of antibodies to detect antigens on the surface of bacteria that have been shown demonstrate antigenic variability (12,149,210). Serotyping methods have been used for decades for the taxonomic grouping of a number of bacterial pathogen species and remain important for typing Salmonella, Legionella, Shigella, and Streptococcus pneumoniae isolates.…”
Section: Phenotypic Methodsmentioning
confidence: 99%
“…Based upon agglutination profiles, the serotype is determined. Additionally, for organisms such as S. pneumoniae the quellung test is used, in which test antibodies bind to the corresponding capsular antigens and induce swelling of the capsule, which can be observed with microscopy (12).…”
Section: Phenotypic Methodsmentioning
confidence: 99%
“…Serotypes differ substantially in their prevalence (3)(4)(5), their tendency to cause diseases (6)(7)(8)(9), and their degree of antimicrobial resistance (10,11). Notably, the most common serotypes in both invasive disease and carriage exhibited overall consistency across populations and time (4) until the recent widespread use of pneumococcal conjugate vaccines (PCV7, PCV10, and PCV13) (12,13).…”
mentioning
confidence: 99%
“…Serotypes differ substantially in their prevalence (3)(4)(5), their tendency to cause diseases (6)(7)(8)(9), and their degree of antimicrobial resistance (10,11). Notably, the most common serotypes in both invasive disease and carriage exhibited overall consistency across populations and time (4) until the recent widespread use of pneumococcal conjugate vaccines (PCV7, PCV10, and PCV13) (12,13). While PCV7 successfully reduced the burden of invasive pneumococcal disease (14), specific serotypes not targeted by the vaccine, such as 19A and serogroup 15, have been reported to increase in both carriage and invasive disease (15)(16)(17)(18).…”
mentioning
confidence: 99%
“…Studies examining the contribution of the capsular type to virulence have demonstrated that only a small subset of serotypes cause the majority of IPD; serotypes 4, 6A, 6B, 14, 23F, 19F, 9V, and 18C account for 80% of the invasive isolates acquired from children 2 to 5 years of age in the United States (5,13). More recently, molecular typing, such as pulsed-field gel electrophoresis of restriction fragments and multilocus sequence typing, has refined this observation, determining that within invasive serotypes, invasive and noninvasive clones exist (35,42).…”
mentioning
confidence: 99%